2019
DOI: 10.3224/zff.v31i3.06
|View full text |Cite
|
Sign up to set email alerts
|

A different perspective on exogamy: Are non-migrant partners in mixed unions more liberal in their attitudes toward gender, family, and religion than other natives?

Abstract: Classic assimilation theory perceives migrant-native intermarriage as both a means to and a result of immigrants’ integration processes into host societies. The literature is increasingly focusing on marital exogamy of immigrants, yet almost nothing is known about their native partners. This explorative study contributes to the literature on migrant integration and social cohesion in Europe by asking whether the native partners in exogamous unions have different attitudes toward gender equality, sexual liberal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 92 publications
(62 reference statements)
1
8
0
Order By: Relevance
“…Our focus was on the potential effects of the ethnically diverse partner/marriage market on members of the non-migrant mainstream population. To the best of our knowledge, our study is the first contribution to the research on mixed unions, and not just for Germany [ 7 , 10 , 75 , 76 , 80 ], that uses quantitative representative data to focus on the non-migrant partner, and to examine their gendered employment patterns. Most previous research on this topic has focused primarily on the migrant partner in such unions who crossed social boundaries between migrant minority and majority groups by marrying a member of the majority, which may have facilitated the process of becoming part of the host society [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our focus was on the potential effects of the ethnically diverse partner/marriage market on members of the non-migrant mainstream population. To the best of our knowledge, our study is the first contribution to the research on mixed unions, and not just for Germany [ 7 , 10 , 75 , 76 , 80 ], that uses quantitative representative data to focus on the non-migrant partner, and to examine their gendered employment patterns. Most previous research on this topic has focused primarily on the migrant partner in such unions who crossed social boundaries between migrant minority and majority groups by marrying a member of the majority, which may have facilitated the process of becoming part of the host society [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although much of this literature has focused on attitudes toward gender equality and related behavior, to the best of our knowledge, no existing study has examined gendered employment patterns in mixed unions in the majority group by applying a couple perspective; i.e., by looking at the non-migrant and his/her partner. A recent study on non-migrants in several European countries explored individual attitudes of non-migrants in exogamous and endogamous unions toward gender equality [ 10 ], and found that non-migrants in mixed unions were more supportive of gender equality than their counterparts in endogamous unions. This finding contradicts the stereotyping that often occurs in the media [ 108 ] or in research on mixed marriages, such as studies on German men who are married to women from Asia [ 66 ] or on German women who are in romantic relationships with men from Sub-Saharan Africa [ 11 ].…”
Section: Employment Patterns Gender Roles and Institutional Influencementioning
confidence: 99%
See 2 more Smart Citations
“…(Hwang 2013), and there are gendered patterns therein, for example, white men have preferences for Asian women and white women have preferences for black men (Feliciano, Robnett, and Komaie 2009; Robnett and Feliciano 2011). Braack and Milewski (2019) show that natives in cross‐national unions are more open to sexual liberalization and gender equality. Spurred on by the evidence on gender asymmetries in the marriage market, we examine cross‐national couples in two high‐income countries that have sufficiently detailed microdata to count on individual countries: the United States and Spain.…”
Section: Introductionmentioning
confidence: 99%